Mineral concentrations in the total saliva collected with a new technique from sheep - DUA, K (The Indian Journal of Animal Sciences, 2014)
In the present study the total collection of saliva in sheep was done by a new technique. In it the salivary collector was slipped at the base of the oesophagus in the rumen fistulated sheep and total saliva was collected by a continuous suction. With this technique a large volume of clear and uncontaminated total saliva can be collected which is quite useful in case of clearance studies. The concentrations of magnesium, calcium, sodium, potassium and the phosphorus were estimated in plasma and total saliva. Excretion of these minerals from plasma to saliva was discussed.